A tri-phenomenon perspective to mitigate MOOCs' high dropout rates: the role of technical, pedagogical, and contextual factors on language learners' L2 motivational selves, and learning approaches to MOOC - Amir Reza Rahimi (Smart Learning Environments, 2024)
Abstract MOOC attrition rates have become a research hotspot in open and online education, requiring researchers to pinpoint psychological, technological, pedagogical, and technical factors that could mitigate this problem. For this aim, the current study applied a tri-phenomenon approach to explore language learners' perceptions of support coupled with the moderation role of their motivation plays in shaping their learning approaches to MOOC. To do so, 428 language learners who completed their online language course on the Iranian MOOC platform answered the study survey before getting their course certificate. An analysis of structural equation modeling (SEM) revealed that MOOC instructional and peer support were positively correlated with learners' deep approach while negatively correlated with the surface one. Although technical support was provided in this instance, it did not contribute to shaping language learners' motivation and deep approach. Moreover, language learners who attended MOOCs to learn language intrinsically perceived more instructional support, whereas language learners who joined these courses to pass some obligations or get course certificates perceived greater peer support that could help them pass such criteria and shape their deep approach to MOOC. Further, both types of motivation significantly mediate learners' instructional and peer support within their deep language learning approach in MOOC. As a result of these findings, both theoretical and practical contributions have been reported in the study to lead MOOCs' enrolment to have a deep approach.